Polymerase processivity and termination on Drosophila heat shock genes. - Giardina, C.; Lis, J.T. (Journal of Biological Chemistry, 1993)
5,6-Dichloro-1-beta-D-ribofuranosylbenzimidazole (DRB) limits RNA polymerase II transcription to a gene's 5'-end. Transcription of the uninduced Drosophila hsp70 gene is likewise restricted to the 5'-end, where the polymerase resides in a paused state. Furthermore, paused elongation complexes formed on the uninduced hsp70 gene and in DRB-inhibited reactions can both be restarted by Sarkosyl or high salt. These similarities prompted us to explore whether these complexes were generated by a block at the same polymerase modification step. In vivo UV cross-linking and KMnO4 hyperreactive site mapping show that while the naturally paused polymerase is restricted to the first approximately 42 base pairs of hsp70, DRB treatment of heat-induced cells allows the polymerase to transcribe past this site. Therefore, the DRB-sensitive step is probably not rate-limiting for hsp70 transcription under uninduced conditions. DRB treatment did, however, lead to the reduction of KMnO4 hyper-reactivity on hsp70 and hsp26 in a region correlating with open polymerase and/or early elongation complexes, suggesting a site for the DRB-sensitive polymerase modification step. Finally, we used the techniques of polymerase-DNA cross-linking and KMnO4 hyper-reactive site mapping to analyze the natural polymerase termination process at the 3'-end of the hsp26 gene. The data obtained are consistent with polymerases terminating at multiple sites downstream of the polyadenylation site.